2006
DOI: 10.1300/j010v43n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Mindfulness-Based Stress Reduction (MBSR) Program for Caregivers of Children with Chronic Conditions

Abstract: This brief MBSR program for caregivers of chronically ill children was successful in significantly decreasing substantial stress symptoms and mood disturbance. Further studies would benefit from using more rigorous methodology and applying the program to other groups of chronically stressed caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
83
3
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 19 publications
7
83
3
4
Order By: Relevance
“…MBIs have also been used to reduce psychological distress among medical students (Rosenzweig et al 2003;Shapiro et al 1998), nurses (Beddoe and Murphy 2004;Mackenzie et al 2006), therapists in training (Shapiro et al 2007), survivors of child abuse (Kimbrough et al 2010), caregivers of children with chronic conditions (Minor et al 2006), and cancer patients and survivors (Foley et al 2010;Lengacher et al 2009;Speca et al 2000). Other studies have examined the potential of MBIs to improve overall well-being (Ando et al 2011) and health-related quality of life (Roth and Robbins 2004), to reduce fatigue and decrease anxiety related to Chronic Fatigue Syndrome (Surawy et al 2005), and to improve the quality of interpersonal relationships (Carson et al 2004).…”
Section: Mindfulness For Health/mental Health Problemsmentioning
confidence: 99%
“…MBIs have also been used to reduce psychological distress among medical students (Rosenzweig et al 2003;Shapiro et al 1998), nurses (Beddoe and Murphy 2004;Mackenzie et al 2006), therapists in training (Shapiro et al 2007), survivors of child abuse (Kimbrough et al 2010), caregivers of children with chronic conditions (Minor et al 2006), and cancer patients and survivors (Foley et al 2010;Lengacher et al 2009;Speca et al 2000). Other studies have examined the potential of MBIs to improve overall well-being (Ando et al 2011) and health-related quality of life (Roth and Robbins 2004), to reduce fatigue and decrease anxiety related to Chronic Fatigue Syndrome (Surawy et al 2005), and to improve the quality of interpersonal relationships (Carson et al 2004).…”
Section: Mindfulness For Health/mental Health Problemsmentioning
confidence: 99%
“…Less research has been conducted on the effectiveness of mindfulness for caregivers; however, studies that have looked into this area have found positive results (e.g. Epstein-Lubow, McBee, Darling, Armey, & Miller, 2011;Hou, et al, 2013;Minor, Carlson, MacKenzie, Zernicke, & Jones, 2006;Whitebird et al, 2012). This study suggests that mindfulness may be helpful for individuals living with a depressed person, in order to help them move towards a position of safe uncertainty, although…”
mentioning
confidence: 99%
“…Mindfulness-based interventions have been shown to be an effective method of reducing stress and improving wellbeing among a variety of populations (Chiesa and Serretti 2011;Kallapiran et al 2015;Khoury et al 2013;Piet et al 2012) including caregivers (Altmaier and Maloney 2007;Birnie et al 2010;Bögels et al 2008Bögels et al , 2014Epstein-Lubow et al 2011;Minor et al 2006; Van der Oord et al 2012;Whitebird et al 2012). Mindfulness is defined as "purposefully paying attention and being present in the moment" (Kabat-Zinn 2003, p. 145).…”
Section: Introductionmentioning
confidence: 99%